Literasi Ekonomi dan Pengelolaan Keuangan Pribadi di SMK Nurcahaya Medan - Retno Nela Simanjuntak; Nova Lega Hati Siregar; Muhammad Harpis (Lembaga Pengembangan Kinerja Dosen, 2025)
Economic literacy education and personal financial management have an important role in preparing the younger generation to face future economic challenges. The aim of this service is to increase students' understanding of SMK Nurcahaya Medan about economic literacy and how to manage personal finances effectively. This activity is carried out through counseling, interactive discussions and financial management simulations. The results of this activity show an increase in students' knowledge regarding basic economic concepts, budget management, and the importance of financial planning. With this activity, it is hoped that students can practice wise financial management in everyday life.